Wizerunek prasowy i internetowy instytucji kościelnej a linia redakcyjna – casus Fundacji „Dzieło Nowego Tysiąclecia” - Leśniczak, Rafał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The author has analyzed the image of the “Work of the New Millennium” Foundation in nationwide weekly magazines “Gość Niedzielny”, “Newsweek Polska”, “W Sieci” and on the websites http://gosc.pl, http://www.newsweek.pl and https://www.wsieciprawdy.pl. An attempt was made to determine to what extent the editorial line of the above-mentioned press titles and websites affects the presentation of ecclesiastical institutions. The analysis covered paper editions and websites of Polish opinion-forming weeklies, which are among the most influential and, at the same time, representing a different profile: Catholic and secular (left liberal and right-wing). The author used the method of press content analysis. Press studies confirmed the catholic profile of the “Gość Niedzielny”, while in the case of secular press titles, there was no reference to the topic of the foundation, which prompted the author to try to explain such a research result based on media studies.
The Press and Internet image of Church Institution and the editorial line – case study of the “Work of the New Millennium” Foundation
Keywords: image; press; opinion-forming weeklies; foundation